Practical Research Methods For Media And Cultural Studies : Making People Count - Davies, Maire Messenger, Mosdell, Nick (Edinburgh University Press, 2006)
This book is for people who think they can’t do numbers and moreover don’t want to do them, perhaps because ‘doing numbers’, in the form of studying mathematics at school, has been associated with feelings of struggle, bewilderment and incompetence. For many such people, even if numbers eventually were mastered, numerical form ulae still seem less adequate at explaining the complexity of the wo rld, or of personal experiences, than language or artistic forms. This sense of inadequacy and boredom with numbers can be uncom- fortable for bright, imaginative young people, used to succeeding intellectually in other areas of the curriculum based on linguistic and creative skills, such as English, history and the arts. Such feelings can lead to rejection and suspicion of any kind of knowledge which is based on the systematic acquisition of data analysed in numerical form ;w e have found this to be the case with many students and col- leagues throughout our careers. Yet much of the everyday knowledge we all have about the world does come in numerical form, or can be translated into that form for easier manipulation and prediction. Often we do not realise that when we ‘calculate the odds’, we are dealing in mathematical probabilities, or that when we make value judgements about what is ‘best’, ‘better’ or ‘worse’, we are manipu- lating ‘ordinal data’.